The current Nordic biogas and biofertilizer potential : An inventory of established feedstock and current technology - Lindfors, Axel; Feiz, Roozbeh (Linköpings universitet, Industriell miljöteknik, 2023)
Biogas solutions in the Nordics is undergoing rapid developments and the demand for biogas is ever increasing because of the Russian war on Ukraine and the transition to fossil free industry and transportation. Furthermore, with the introduction of several multi-national companies into the biogas sector in the Nordics and with more and more biomethane being traded across national borders, it becomes increasingly important to view biogas solutions in the Nordics as a whole and to go beyond the confines of each individual nation. Since the transition and the current energy crisis require a quick response, understanding what could be done with current technologies and established substrates is important to guide decision-making in the short-term. This study aims to do just that by presenting the current biogas potential for the Nordics, including Denmark, Finland, Iceland, Norway, and Sweden. The potential was estimated for eight categories: food waste, manure, food industry waste, sludge from wastewater treatment, landscaping waste, straw, agricultural residues, and crops with negligible indirect land use effects (such as ley crops and intermediary crops). Two categories were excluded due to a lack of appropriate estimation procedures and time to develop such procedures, and these were marine substrates and forest industry waste. Furthermore, several categories are somewhat incomplete due to lack of data on the availability of substrates and their biogas characteristics. These include, for example, crops grown on Ecological focus areas, excess ley silage, damaged crops, and certain types of food industries. The specifics of each category is further detailed in Section 2 of the report. In the report, the biogas potential includes the biomethane potential, the nutrient potential, and the carbon dioxide production potential, capturing all outputs of a biogas plant. The results of the potential study show that the current biomethane potential for the Nordics is about 39 TWh (140 PJ) per year when considering the ...